Temples Thrived As Corporations And Multifarious Social Activities (Journal of Pharmaceutical Negative Results, 2022)
In the medieval period, in variably the temples of Tamil country played a significant role in the social life of the people and social activities centred on the temples. The temples were served as corporations, founded with the full co-operation of the local existing social strata. This paper throws light on the inscriptions found in these temples, which describe the social structure of those days, the devoted patronage from the ruling Kings, their subordinates and the irrespective of the social strata of medieval Tamilaham.